Criminal Sanctions Against Perpetrators of Illegal Logging According to Positive Law and Islamic Law (Case Study of Cases at the Jambi District Court) - Prasetyo, Teguh Santiko (CV. Rayyan Dwi Bharata, 2024)
This research was conducted to find out how the Judge's legal considerations were for perpetrators of illegal logging in decision Number 601/Pid.Sus/2017/PN.Jbi and how the Islamic criminal law analysis of the Judge's considerations in deciding case Number 601/Pid.Sus/2017/PN. Jbi. The data sources for this research were collected by studying documents, case files and library materials. The research results show that the legal basis used as a judge's consideration in imposing sanctions on perpetrators of illegal logging crimes is the demands of the Prosecutor/Public Prosecutor, namely the crime in Article 83 paragraph (1) letter b in conjunction with Article 12 letter e of RI Law No. 18 of 2013 concerning Prevention and Eradication of Forest Destruction, with a prison sentence of 1 (one) year in prison reduced to the time the defendant is in temporary detention with an order that the defendant remain in detention and a fine of Rp. 500,000,000,- (five hundred million rupiah) subsidiary 3 (three) months in prison, and the judge decided on this crime with a sentence of 1 year in prison and a fine of Rp. 500,000,000,- (five hundred million rupiah). In Islamic criminal law, the criminal act of illegal logging (Illegal Logging) committed by the defendant is included in the category of jarimah ta'zir because there are no provisions in the text regarding this criminal act. Judges in this case are given the authority to impose sentences and can take various forms of punishment that can make the perpetrator of the crime worse, the aim is none other than to deter him from repeating his mistakes, such as caning, cutting off his hand, being imprisoned or detained, and others that adjusted according to the error rate.